Pandangan netizen terkait childfree oleh Gita Savitri Devi - Syaharani, Devita (Maliki Interdisciplinary Journal, 2024)
This research aims to describe netizens' responses to the childfree phenomenon which is currently being widely discussed by the public as a result of comments made by an influencer named Gita Savitri Devi. The term "Childfree" is used to refer to someone who wants to live without having children. This lifestyle is in contrast to the norms that apply in Indonesia, where religious and traditional factors strongly recommend having children, even if only one. This research uses a qualitative approach with a phenomenological focus. The research results show that society responds to this phenomenon with various dimensions which can be categorized into two main perspectives, namely socio-cultural and religious perspectives. The community's response from a cultural perspective states that the status and existence of women in the past was seen based on their capacity to bear children, reflecting the pattern that exists in Indonesian society where married couples are encouraged to have children, even if only one. Meanwhile, from a religious perspective, having children is recommended in Islamic teachings, not an obligation. Therefore, the decision to live a childfree lifestyle cannot be classified as a prohibited act, because every married couple has the right to plan and manage the dynamics of their family life, including considering whether or not to have children.